Analisis Pengaruh Pengeluaran Pemerintah, Jumlah Tenaga Kerja, dan Tingkat Pendidikan terhadap Pertumbuhan Ekonomi di Kota Surakarta Tahun 1991 - 2013 - Anggraeny, Alvia Ayu; , Drs.Triyono, M.Si (2016)
This study entitled "Analysis of Effect of Government Spending, Total Manpower Education in Surakarta Year 1991-2013" The aim of this study was to measure and analyze the effect of government spending, employment and level of education to economic growth in the city of Surakarta in 1991- 2013. Data used in this research is secondary data, economic growth, government spending, employment and education levels in Surakarta, metodeanalisis used was Ordinary Least Square (OLS) is to determine the direction and magnitude of the effect of the free variable ( independent) related to variable (dependent). The results of this study can be concluded that the variable labor there is no significant negative effect on the economy, while variable variable levels of education and government spending significant positive effect on the economic growth of the city of Surakarta.